Jaka tożsamość kulturowa dla dzisiejszej Europy? - Skrzypczak, Katarzyna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The present article addresses the question of cultural identity of today’s Europe and the shape it should take. Such issues as relation between European identity and national identities in the context of the continent’s cultural diversity are considered from interdisciplinary perspective. Two paradigms presented in the article: the essentialist and constructivist approach to identity serve as a starting point for reflection on the basis of the European identity as well as on its future form.